INTEGRATION OF INNOVATION AND TRADITION: COMPETITIVE ADVANTAGES OF ISLAMIC BOARDING SCHOOLS IN THE WORLD OF EDUCATION - Alfin, Vian Miati; Zakiyah, Kuni; Badria, Badria; Elsanda, Elit; Muslifah, Muslifah; Husna, Ilaika Samaul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze how Islamic boarding schools have succeeded in integrating religious education traditions with modern innovations in order to maintain the relevance of their education in the digital era. Islamic boarding schools, which are known for their yellow book-based teaching systems and deep understanding of the Islamic religion, are now faced with the challenge of maintaining the authenticity of traditions while accommodating technological developments. The main findings of this research show that Islamic boarding schools not only maintain traditional teaching methods, but also adopt modern educational technology innovations, such as the use of digital platforms (WhatsApp, Zoom) to expand the reach and flexibility of learning, without reducing the face-to-face interactions that are essential in Islamic boarding school education. Other innovations are also implemented in the operational management of Islamic boarding schools through digital systems for data management, finances and internal activities, which increase efficiency and transparency. This research also highlights the role of Islamic boarding schools in preserving Islamic culture and local traditions, by utilizing technology to document and promote this culture to a wider audience. Overall, this research shows that the integration of innovation and tradition in Islamic boarding schools allows them to remain relevant as educational institutions and centers for preserving Islamic culture that are adaptive to current developments.